The discrete Langevin machine: bridging the gap between thermodynamic and neuromorphic systems - Kades, Lukas; Pawlowski, Jan M. (Arxiv, 2019)
A formulation of Langevin dynamics for discrete systems is derived as a new class of generic stochastic processes. The dynamics simplify for a two-state system and suggest a novel network architecture which is implemented by the Langevin machine. The Langevin machine represents a promising approach to compute successfully quantitative exact results of Boltzmann distributed systems by LIF neurons. Besides a detailed introduction of the new dynamics, different simplified models of a neuromorphic hardware system are studied with respect to a control of emerging sources of errors.